Als we het zouden weten - Czisch Lataster, Petra; Lataster, Peter (Netherlands : Lataster Films, 2007)
“If We Knew” is a documentary about pediatricians who work in an intensive-care unit for premature infants at Groningen’s University Hospital. A film essay about the compassion needed to heal the sick and also occasionally needed to hasten the death of a sick child who is suffering unbearably and without hope. Thanks to modern technology doctors can do more and more to cure patients or ease pain where it is unbearable. As a consequence they have to ask themselves if every human being who can be kept alive will lead a life worth living. Should every life be saved at whatever cost? “If We Knew” shows a group of pediatricians cope with tough ethical questions and the impossible decisions they have to make.
Verzio Film Festival Submission
Verzio Film Festival Submission
Keywords: Documentary films